2013
DOI: 10.1155/2013/932013
|View full text |Cite
|
Sign up to set email alerts
|

Stability Prediction of Milling Process with Variable Pitch Cutter

Abstract: The use of variable pitch cutter is a known means to increase the stable limit depth of cut by disrupting the regenerative effect. In this paper, an improved semidiscretization algorithm is presented to predict the stability lobes for variable pitch cutters. Modeling efforts develop a straightforward analytical integral force model that can cover any case of piecewise continuous cutting regions regarding the helix angle. The proposed approach has been verified with the comparisons with prior works, time domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
(40 reference statements)
0
19
0
Order By: Relevance
“…However, most of them were developed with the aim of constructing stability charts for milling processes, such as the analysis of the milling system with runout [25], with variable pitch/helix cutter [26][27][28][29][30], with variable-spindle speed [31][32][33], or with serrated cutter [34,35]. In order to verify the proposed method, two typical milling operations are chosen and considered.…”
Section: Verification Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of them were developed with the aim of constructing stability charts for milling processes, such as the analysis of the milling system with runout [25], with variable pitch/helix cutter [26][27][28][29][30], with variable-spindle speed [31][32][33], or with serrated cutter [34,35]. In order to verify the proposed method, two typical milling operations are chosen and considered.…”
Section: Verification Of Methodsmentioning
confidence: 99%
“…For the variable pitch cutter as shown in Figure 4(b), two methods gain consistent predicting results, except for the high-speed domain at approximately 8500 rpm, where a clear deviation occurred. Reference [27] chose one point ( = 5 mm and Ω = 8500 rpm) in this deviation and showed its stabilization by time-domain simulations. The reason of this phenomenon is as follows.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Jin et al . used an improved SD algorithm that examines the effect of the tool geometries on the stability trends for variable pitch or variable helix milling.…”
Section: Introductionmentioning
confidence: 99%
“…Dombovari and Stepan [19] introduced a general SDM-based mechanical model to predict the linear stability of special cutters with optional continuous variation of the helix angle and showed that special instability lenses occur and decrease in size in the stability chart. Jin et al [20,21] used an improved SD algorithm that examines the effect of the tool geometries on the stability trends for variable pitch or variable helix milling.…”
Section: Introductionmentioning
confidence: 99%
“…The semidiscretization method is not noted for any major shortcoming even though Henninger and Eberhard [33] pointed out avenue for improved computational efficiency and accuracy. The semi-discretization method has also been used in stability analysis of more advanced milling models that include effects like process damping [34][35][36], tools with non-uniform pitch [37][38][39], variable helix end-mills [25,[38][39][40][41], spindle speed variation [42,43], serrated milling tools [44] and tool run-out [45]. The method of temporal finite element analysis was introduced in a study of stability of interrupted cutting by Bayly et al [46].…”
Section: Introductionmentioning
confidence: 99%